Robust Watermarking Scheme Using Chinese Remainder Theorem-Based Error Correcting Codes - Goh, Vik Tor (2005)

(untitled)
One of the more promising technologies that can be used to curtail the illegal usage of copyrighted contents is digital watermarking. A robust watermarking scheme using error correcting codes is proposed. In this block-based scheme for greyscale images, relationships between blocks of pixels are exploited to inconspicuously embed the watermark. Furthermore, watermark recovery is performed without the need of the original image watermark. The robustness of the watermarking scheme is tested for various image manipulation techniques.